Blessing or curse? Domestic plants survival and employment prospects after foreign acquisition - Sourafel Girma; Holger Görg (Leverhulme Centre for Research on Globalisation and Economic Policy, University of Nottingham, 2001)
This paper investigates whether the acquisition of a domestic establishment by a foreign owner has any effects, positive or negative, on the survival prospects and employment growth of that plant. The empirical analysis uses data from the Annual Respondents Database (ARD) for the UK electronics industry for the period 1980 to 1993. Estimating a standard hazard model including a dummy variable for the incidence of acquisition yields the result that foreign takeover reduces the lifetime of the acquired plant. Estimations of the determinants of employment growth in domestic plants provide some evidence that the incidence of takeover reduces employment growth, in particular for unskilled labour. Both survival and employment growth estimations do not appear to be subject to endogeneity problems.
Keywords: 330; Direktinvestition; Elektronikindustrie; Beschäftigungseffekt; Großbritannien